Pengaruh Upah Minimum terhadap Employment Transition: Analisis Level Individu di Pulau Jawa - Beni Teguh Gunawan (Pusat Penelitian dan Pengembangan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2018)
The objectives of the study is to determine the effect of minimum wages on employment transition, especially in Java as the majority of the Indonesian region set a minimum wage in district/city level. Previous similar studies carried out in developed countries that do not take the informal sectors. The analysis was performed using individual data sourced from Sakernas BPS 2010 and 2015 are seen as a form of longitudinal t-1 and t for each year. Empirical analysis used is multinomial logit with markov chain approach. In addition to a real minimum wage as an primary independent variable, other independent variables used were age, gender, educational level, and marital status as individual characteristics, as well as the GRDP, the share of themanufacturing sector in the GRDP, coverage of the minimum wage, and the ratio of working age population to total population as regional characteristics. Minimum wage has a significant and negative impact on the transition from the informal to the formal (F to I), formal to not employed (F to N), and not employed to not employed (N to N). In addition, the minimum wage is also positive and significant impact on the transition fromformal to formal (F to F) and informal to informal (I to I). While the transition from not employed to informal (N to I) are not affected by the minimum wage. Empirical evidence shows that the impact of minimum wage on employment transition pattern in Indonesia is closest to monopsony market.